Ownership of unlawful wealth from Islamic legal perspective - Ibrahim, Badruddin; Mohd, Azizah (IDOSI Publications, 2017)
This study examines the issue of ownership of unlawful wealth under Islamic law. The question is whether unlawful wealth either with respect to its substance or its acquisition is legally owned under Islamic law. In another words, whether Islam legally recognizes unlawful wealth with respect to ownership. The study examines the concept of ownership and means of acquiring ownership; and the concept of unlawful wealth and its position under Islamic law. The discussion extends to the position of unlawful wealth with respect to ownership particularly the wealth which is acquired by unlawful means like gambling, trading of unlawful substance, bribery etc. The research is a library research where the issue will be examined from the perspective of the Qur’an and the Sunnahas primary sources of Islamic law and follows with the examination of the view of Muslim jurists of four well known schools of law as well as the view of contemporary Muslim scholars. It is hoped that the study may provide a clear reference and guideline regarding the concept of ownership and unlawful wealth in Islamic law that is significant and beneficial to all in our present day.